Catalytic Performance of Coal Char for the Methane Reforming Process. Issue 1 (27th November 2014) - He, Tao; Sun, Zhiqiang; Wu, Jinhu; Xu, Zexi; Zhang, Dongke; Han, Dezhi
Abstract A new concept of combined coal gasification and methane reforming in a single reactor was proposed as an alternative path for syngas production using coal and coalbed methane. Here, the results of this process are summarized. The experimental work was carried out in a fixed‐bed reactor. Methane cracking, CO2/steam reforming of methane over coal char, and the effects of chars made from different types of parent coal on methane conversion were examined. The catalytic effect of coal char on methane cracking and reforming increased with decreasing coalification degree. A synergistic effect was observed in that, while the coal char catalyzed the methane reforming reactions, gasification of the coal char took place simultaneously, which counter‐balanced the deposition of carbon especially for the methane‐steam‐char system.